Rereading the Concept of “Light” in the Holy Quran - Mahmoud Vaezi; Hussein Jeddi (آموزه‌های قرآنی)
The concept of light has a comprehensive and fundamental meaning in Quranic applications and has been used 49 times in different contexts. With thematic contemplation in Qur'anic applications, in addition to the pursuit of light, on both the ontological and epistemological levels, how the cognitive subject is perceived in the perception of “light” is very important. New commentators on the interpretation of the verse of light have tended to be figurative due to the existence of narrative information and intellectual barriers. But another group, after the fifth century, sought to prove the truth of the verse by offering different definitions. This article takes two explanatory-critical approaches to the views of earlier commentators, based on interrogation in Qur'anic applications, in addition to different classifications in the applications of light, inspired by Qur'anic linguistic findings, on how to attribute “the light of God”. Therefore, although the light of the Almighty God falls into the category of transcendental light, it has a transcendent and expanded level. This perfection of the appearance of the Almighty God’s light must be understood, in addition to the removal of the various veils of darkness and light, with the inner realm of man, the “heart”.